KUALITAS SEMEN SAPI LIMOUSIN SELAMA PENDINGINAN MENGGUNAKAN PENGENCER CEP-2 DENGAN PENAMBAHAN BERBAGAI KONSENTRASI SANTAN - Pramudya Annisa Firdausi; Trinil Susilawati; Sri Wahyuningsih (Jurusan Produksi Ternak, Fakultas Peternakan, Universitas Brawijaya, 2014)
This research was carried out at Laboratory of Balai Besar Inseminasi Buatan, Singosari, Malang start from 8th May until 27th May 2014. Research was to find the effect of liquid semen of Limousin during chilled preservation. Semen divided into four with 5%, 10%, 15%, coconut milk (P1=CEP-2+5% S, P2=CEP-2+10% S, P3=CEP-2+15% S) and 10% egg yolk (P0=CEP-2+10% KT), gave the best result in P0 and has highly significant different (P<0,01) than others treatments, listed from higher to the lower from P2, P1, and P3 then motility after 24h were analysis with Pearson’s Chi- Square and used to compare total motile sperm count with expected value 40 million cells/mL showed that egg Yolk gave the superior effect on sperm quality after 24h preservation. The motiity, viability, and abnormalitas in CEP-2+ Coconut Milk has highly significant different (P<0,01) lower compared to CEP-2+ 10% KT. The various level extender of coconut Milk in CEP-2 can’t maintain the sperm quality as well as egg yolk, but P2 had shown best ability of maintain sperm quality and total motile sperm Key Words : Semen, extender, preservation, coconut Milk, and egg yolk